Species richness, relative abundance, and habitat of reproduction of terrestrial frogs in the Triângulo Mineiro region, Cerrado biome, southeastern Brazil - Giaretta, Ariovaldo A. (2008)
Based on field observations and pitfall sampling, we determined the species richness, relative abundance, and reproductive habitat of terrestrial frogs in three municipalities in the Triângulo Mineiro region, south Cerrado biome, in southeastern Brazil. We found thirty-two species of terrestrial frogs, belonging to the families Brachycephalidae, Bufonidae, Cycloramphidae, Dendrobatidae, Leiuperidae, Leptodactylidae and Microhylidae. Most of the species were found in open areas and reproduced in human-generated environments, such as artificial lakes (10 species) and ponds (14 species). Dominance was high, with Physalaemus cuvieri Fitzinger, 1826 (Leiuperidae) representing 48% of sampled frogs. A larger number of individuals was captured in the wet season, when most of the species were reproducing. Compared to other areas of Cerrado biome, the Triângulo Mineiro sites presented a larger number of species, which may be attributed to the larger sampled area and greater sampling effort, lower altitude and presence of human generated habitats. The richness of terrestrial frogs was also larger than that in some forested localities in southeastern Brazil, indicating that the number of species cannot be explained only by precipitation and type of vegetation cover. The greater abundance of individuals during the wet season may be related to a greater movement of adults to breeding sites and to juvenile recruitment/dispersion. The heterogeneity of environments in the Cerrado biome, including its several isolated highlands, contributes to its high (local and regional) diversity of frogs.